Mannose 6-phosphate Receptor (MPR 300) Proteins from Goat and Chicken Bind Human IGF-II. Issue 2 (22nd June 2006) - Koduru, Suresh; Yadavalli, Sivaramakrishna; Nadimpalli, Siva Kumar
Abstract : Mannose 6-phosphate receptor proteins (MPR 300 and 46) in mammals have been shown to mediate transport of lysosomal enzymes to lysosomes intracellularly. Both receptors are also expressed on the plasma membrane. Only MPR 300 protein on the plasma membrane has been shown to be a multifunctional protein which in addition to binding mannose 6-phosphate containing proteins also binds human insulin-like growth factor-II (IGF-II) causing its internalization [Hille-Rehfeld, A. (1995) Mannose 6-phosphate receptors in sorting and transport of lysosomal enzymes. Biochim. Biophys. Acta. 1241 : 177–194]. This property has been shown to be exhibited by other mammalian receptors but not by the chicken and frog receptors. In a recent study however it was shown that the fish embryo MPR 300 binds human IGF-II. [Mendez, E., Planas, J.V., Castillo, J., Navarro, I. and Gutierrez, J. (2001) Identification of a type II insulin-like growth factor receptor in fish embryos. Endocrinology, 142 : 1090–1097]. In the present study, we demonstrate that the purified goat and chicken liver receptors bind human IGF-II by employing cross-linking experiments (purified receptors and radiolabeled IGF-II) and by ligand blotting (using purified receptors and biotinylated IGF-II). Further CEF cells (chicken embryonic fibroblasts) that are known to contain the putative MPR 300 protein were employed to demonstrate that the CEF cell receptor binds human IGF-II.